Informatics opportunities to involve patients in hospital safety: a conceptual model. (3rd October 2019) - Haldar, Shefali; Mishra, Sonali R; Pollack, Ari H; Pratt, Wanda
Abstract: Objective: Inpatients could play an important role in identifying, preventing, and reporting problems in the quality and safety of their care. To support them effectively in that role, informatics solutions must align with their experiences. Thus, we set out to understand how inpatients experience undesirable events (UEs) and to surface opportunities for those informatics solutions. Materials and Methods: We conducted a survey with 242 patients and caregivers during their hospital stay, asking open-ended questions about their experiences with UEs. Based on our qualitative analysis, we developed a conceptual model representing their experiences and identified informatics opportunities to support patients. Results: Our 4-stage conceptual model illustrates inpatient experiences, from when they first encounter UEs, when they could intervene, when harms emerge, what types of harms they experience, and what they do in response to harms. Discussion: Existing informatics solutions address the first stage of inpatients' experiences by increasing their awareness of potential UEs. However, future researchers can explore new opportunities to fill gaps in support that patients experience in subsequent stages, especially at critical decision points such as intervening in UEs and responding to harms that occur. Conclusions: Our conceptual model reveals the complex inpatient experiences with UEs, and opportunities for new informatics solutions to support them at all stages of their experience. Investigating these new opportunities could promote inpatients' participation and engagement in the quality and safety of their care, help healthcare systems learn from inpatients' experience, and reduce these harmful events.